A Basic Interpretative Study of the Lived Experiences of Secondary School Leaders in Georgia Who Have Used Online Credit Recovery to Assist At-Risk Students Graduate - Gross, Deidrienne, Nicole (My University, 2024)
Increasing and sustaining student achievement is the hallmark of the U.S. educational system. The school principal must keep the mission and vision of student achievement at the forefront and devise methods to increase high school graduation rates. Online credit recovery is an efficient means to assist secondary students, including at-risk populations, who lack credits due to course failure. This basic interpretive study examined the lived experiences of five secondary leaders in Georgia whose graduation rates increased annually. The purpose of the project was to comprehend the meaning these five leaders made from their experiences utilizing online credit recovery software. Understanding the participants’ lived experiences may provide strategies for stakeholders working with secondary at-risk students. The data were collected through observations, semi-structured interviews, and historical data reviews. Strategies to support students enrolled in online credit recovery programs included providing multiple opportunities for online classes and staffing online credit recovery courses with certified teachers. Teachers' perceptions of non-traditional means of recovering credits after course failure were a barrier. Although the principal is the instructional leader responsible for increasing and sustaining student achievement, helping students, particularly at-risk students, graduate with their cohort requires many staff members. The findings indicate students who are credit deficient require the assistance of compassionate and dedicated staff well-informed of the needs of the at-risk learner. Creating authentic relationships with a caring adult may increase student engagement and familiarity with their school. Forming solid and meaningful connections to school through clubs, homerooms, and viable post-secondary career opportunities may help increase student achievement.
Chapter I. INTRODUCTION 1 Overview 1 Problem Statement 4 Purpose Statement 5 Research Questions 6 Significance of the Study 7 Conceptual Framework 7 Summary of the Methodology 9 Research Design 10 ResearchAssumptions 11 Limitations 11 Delimitations 12 Definitions of Key Terms 13 Summary 14 Chapter II. LITERATURE REVIEW 17 Student Achievement 17 School Reform’s Impact on Student Achievement 19 School Accountability and Student Achievement 23 Statistics on Student Achievement 25 Instructional Leadership as a Critical Factor to Graduation Rates 26 Role of the Instructional Leader 28 The Decline in Student Achievement 29 Impact of Failing Courses 30 Achievement Gaps 31 School. 35 Family. 37 Individual. 39 At-Risk Students 41 Potential Outcomes in School 44 Graduation Rate Calculation 49 Online Credit Recovery 60 Conceptual Framework 72 Finn Participation and Identification Model 72 Implications for School Leaders 76 Role of the School Principal 76 Summary 83 Chapter III. METHODOLOGY .86 Research Questions 86 Research Design 87 Research and Design Rationale 88 Setting 90 Role of the Researcher 92 Methodology 93 Instrumentation 94 Participants 97 Data Collection 98 Data Analysis 103 Miles and Huberman Analytical Method 105 Validity 108 Issues of Trustworthiness 109 Ethical Procedures 110 Summary 112 Chapter IV. FINDINGS .115 Location of Research/Setting 116 Data Collection 119 Participants 120 Summary 163 Chapter V. OVERVIEW OF DATA COLLECTION AND ANALYSIS 165 Themes 166 Relationship Building 167 Student Engagement (Finn Participation Model) 180 Access to Nontraditional Educational Formats. 185 Online Credit Recovery 192 Experience Working with At-Risk Students 204 Instructional Leadership 213 Data 217 Graduation Coach or Similar Personnel 219 Adults as Barriers to Success 223 Finn’s Identification and Participation Model 227 Participation 230 Summary 231 Chapter VI. DISCUSSION AND CONCLUSION 234 Methods and Procedures 238 Interpretation of Findings 239 Research Question 1 241 Research Question 2 242 Multiple Opportunities to Recover Lost Credits 245 Research Question 3 250 Implications of the Study 252 Homeroom 252 Relationship Building 253 Graduation Coach 255 Online Credit Recovery Courses 255 Limitations of the Study 257 Recommendations for Future Research 258 Conclusion 259 REFERENCES 265
Keywords: Dissertations, Academic--United States; Educational leadership; Georgia; Education, Secondary; High school graduates--Rating of; Credit ratings; Academic achievement